Effects of ITPA polymorphism on decrease of hemoglobin during simeprevir, peg‐interferon, and ribavirin combination treatment for chronic hepatitis C. Issue 12 (5th April 2016) - Morio, Kei; Imamura, Michio; Kawakami, Yoshiiku; Morio, Reona; Hatooka, Masahiro; Kan, Hiromi; Fujino, Hatsue; Fukuhara, Takayuki; Kobayashi, Tomoki; Masaki, Keiichi; Ono, Atsushi; Nakahara, Takashi; et al.
Abstract : Aim: Polymorphisms in the ITPA gene influence anemia during peg‐interferon (PEG‐IFN) and ribavirin (RBV) therapy, but their effects during triple therapy with simeprevir, PEG‐IFN, and RBV are not sufficiently known. Methods: We analyzed 212 patients with genotype 1 chronic hepatitis C, who were treated with simeprevir plus PEG‐IFN/RBV triple therapy, and assessed the effect of the ITPA polymorphism on hemoglobin levels and RBV dose reduction. ITPA (rs1127354) and IFNL4 (ss469415590) polymorphisms were genotyped using the Invader assay. A stepwise multivariate regression analysis was carried out to identify factors associated with outcome of the therapy. Results: Reduction of hemoglobin levels was similar between patients treated with simeprevir plus PEG‐IFN/RBV and those treated with PEG‐IFN/RBV therapy. In simeprevir plus PEG‐IFN/RBV‐treated patients, decreases in hemoglobin levels were faster and greater, and the cumulative proportion of patients with ribavirin dose reduction was significantly greater in ITPA genotype CC patients than in CA/AA patients. The total dose of simeprevir and PEG‐IFN was similar between ITPA genotype CC and CA/AA patients. In contrast, the total dose of RBV was lower in patients with the CC genotype. Multivariate analysis showed that the IFNL4 TT/TT genotype, but not the ITPA SNP genotype, treatment history (treatment‐naive or relapse during prior treatment), and treatment completion were significantly associated with outcome of therapy. Conclusion: ITPA polymorphism influences hemoglobin levels and incidence of RVB dose reduction during simeprevir triple therapy, indicating the importance of monitoring anemia during treatment, particularly for ITPA genotype CC patients.